An Error-Proof Approach for Decision Making Using DEMATEL - Islam, A.S.M.Touhidul; Mustafa, Shariman; Sorooshian, Shahryar (KnE Social Sciences, 2019)
Decision Making Trial and Evaluation Laboratory method of Multi-Criteria Decision Making has been being used very widely in many management studies (like Operation Management) to identify causal relationships among factors and draw attention to valuable insight for decision making. The scope of this system has reached the manufacturing industry, social activities, farming, financial system, environmental science, energy, and other areas, and has solved numerous practical problems. However, the author has found that the results are misleading as and when it is applied with global (or overall) consideration or even elements/category of unequal weights. To show the serious differences in the results misguiding decision-makers, an example has been demonstrated in this study. Result of the Decision Making Trial and Evaluation Laboratory from global calculation can be corrected if the calculation and analysis are done based on distinct elements (cluster wise). Grading success or failure factors as per distinct elements of a system and integrating them as per criticality found at the element level, is an added methodology to the existing knowledge of using Decision Making Trial and Evaluation Laboratory. With another example from the previous study, the new approach is justified as well. This new approach will help to find critical factors in a truly holistic way and implement any principles, policies, or system more confidently. Keywords: DEMATEL method; multi-criteria; critical factor; decision making.